Becoming and being: a critical realist study into the emergence of identity in emergency medical science students, and the construct of graduate attributes - Millar, Bernadette Theresa (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2014)
This critical realist thesis seeks to understand how student, graduate and professional identities emerge in Emergency Medical Science (EMS) students at a South African University of Technology (UoT) as well as in professional paramedics in the Emergency Medical Care Services (EMCS). It further considers the construct of graduate attributes (GAs) and its relationship to emergence of identity and influence on curriculum design. The research design is that of a case study. The theoretical framework is critical realism whose depth ontology posits three domains of reality. Causal powers and generative mechanisms exist in the Real domain which cause events or phenomena to emerge in the Actual domain that are experienced in the Empirical domain. Using retroduction one may come to explore some of the causes for the event. Using Bhaskar's concepts of identity, the self, absence and emergence, ontology and four-planar social being, a Bhaskarian explanatory framework of identity to explore the emergence of identity has been created. In exploring graduate attributes, a critical realist question is posed: "What must the world be like for GAs to exist" to explore the possibilities of the existence of GAs. It was found that student identity emerges diachronically in three moments, while professional paramedic identity starts to emerge during the third year of study mainly through the structure, culture and agency of workplace-based learning. In answer to the critical realist question it was found that GAs emerge from the neoliberalist commodification of universities. In seeking an alternative to GAs, traits and attitudes were explored. It was found that these emerge from curriculum, interplay of departmental structure, culture and agency of and from students' being which makes them ontologically radically different from GAs. This study concludes that student, graduate and professional identities emerge from a person's core constellational identity diachronically within four-planar social being and the interplay of structure, culture and agency. GAs cannot be related to the emergence of identity and curriculum design because of their ontology; however, if traits and attitudes are substituted for GAs, a close relationship does exist between emergence of identity, traits and attitudes and curriculum design.
Keywords: Critical realism; Emergency medical personnel -- Psychology; Emergency medical services